2010
DOI: 10.1037/a0020279
|View full text |Cite
|
Sign up to set email alerts
|

Children's contact with their incarcerated parents: Research findings and recommendations.

Abstract: Approximately 1.7 million children have parents who are incarcerated in prison in the United States, and possibly millions of additional children have a parent incarcerated in jail. Many affected children experience increased risk for developing behavior problems, academic failure, and substance abuse. For a growing number of children, incarcerated parents, caregivers, and professionals, parent– child contact during the imprisonment period is a key issue. In this article, we present a conceptual model to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
203
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(218 citation statements)
references
References 73 publications
(151 reference statements)
7
203
0
3
Order By: Relevance
“…Poehlmann et al, 2010), child-friendly visiting environments were more effective at protecting children's emotional wellbeing and existing positive parent-child relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poehlmann et al, 2010), child-friendly visiting environments were more effective at protecting children's emotional wellbeing and existing positive parent-child relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive literature review by Poehlmann et al (2010), just half of the studies revealed a positive association between prison visiting, attachment security 2 and positive emotional outcomes for the child (e.g. self-esteem).…”
Section: Introductionmentioning
confidence: 99%
“…Such contact may occur through visits, phone calls, or letters. Poehlmann, Dallaire, Loper, and Shear ( 2010 ) identifi ed 36 studies conducted after 1998 on incarcerated parent-child contact; of these, nine studies reported on incarcerated maternal outcomes (seven studies found positive and two studies found negative maternal effects) and nine studies reported on child outcomes (four studies found positive, two studies found negative, and three studies found both positive and negative effects). The most common positive outcome examined for incarcerated mothers was improved parent adjustment, such as less maternal "distress," fewer depressive symptoms, more empathy, and less parenting "stress".…”
Section: Introductionmentioning
confidence: 97%
“…Notably, all of the studies included in the Poehlmann et al ( 2010 ) review included self-report measures of stress. As an initial step towards broadening the knowledge base on stress and incarcerated mothers, in the study reported here, we integrated the neurophysiological stress marker cortisol into a battery of self-report measures of maternal psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%
“…They tend to exhibit both internalizing (e.g., depression, withdrawal) and externalizing (e.g., ADHD, stealing, fighting) behaviors (Dallaire, 2007;Fritsch & Burkhead, 1981;Murray & Farrington, 2008;Myers, Smarsh, Amlund-Hagen, & Kennon, 1999;Raimon, Lee, & Gentry, 2009;Turney, 2014), and are more likely to have poor academic performance due to a number of school-re-lated problems including disruptive behavior, suspensions from school, and increased truancy (e.g., Murray & Farrington, 2005;Phillips & Harm, 1996;Raimon et al, 2009;Trice & Brewster, 2004). Also, when their parents are arrested, many children behave in even more emotionally and behaviorally disordered ways, especially when their new caregiving situations are unstable (e.g., Nesmith & Ruhland, 2008;Phillips & Harm, 1997;Poehlmann, 2005a;Dallaire, Loper, Poehlmann & Shear, 2010). The instability of their new caregiving situation is a likely outcome since mothers in prison or jail often have difficult pre-incarceration histories including sexual, physical, and substance abuse, mental illness, medical problems, and homelessness (Glaze & Mauschak, 2008;Mumola & Karberg, 2006).…”
Section: Toward a Decarceral Sexual Autonomymentioning
confidence: 99%